Trend in Financing for Prevention and Control of Non-Communicable Diseases (NCDs) in Thailand, 2002-2012 - Wongwatanakul, Weranuch; Viriyathron, Shaheda; Prakongsai, Phusit (Journal of Health Science of Thailand, 2017)
Over the past decade, there has been a significant increase in burden of disease from non-communicable diseases (NCDs), which were attributed to extremely large amount of both mortality and DALYs loss, in Thailand and worldwide. This documentary research was aimed at exploring the overview of NCD prevention and control in Thailand during 2002-2012. Its objective was also to examine whether expenditure for NCD prevention and control matches with the magnitude of NCD burden. Main data sources were from the National Health Accounts (NHA) of Thailand as well as National Health Sub-accounts for Health Expenditure on Disease Prevention and Health Promotion in 2012. NCD prevention in Thailand has been implemented on both disease prevention and health promotion approaches. Since 2002, the total expenditure on prevention and promotion (TEPP) had been continuously in a rise; however, percentage change of its increasing trend was smaller than that of the total health expenditure (THE) and economic growth. During 2006-2012, though TEPP was increasing, on average, 12.3% per year; it was fluctuated. Both overall TEPP and TEPP for NCDs were mainly for secondary and tertiary preventions; while primary prevention share the minority in overall resources for NCD prevention. Furthermore, impacts from NCDs and their health risk factors were much higher, in terms of estimated cost, than NCD prevention. In addition, economic cost of NCDs was 11 times higher than TEPP for NCD. Therefore, it is extremely important for the Thai government to scale up its priority in NCD prevention and control. Government budget should be increased at least as high as an increasing percentage change in THE. It is also important to increase budget for primary prevention and public health interventions rather than secondary and tertiary prevention. Moreover, for better governance in NCD prevention, there should be a strong political support in re-allocation of health professionals and building specific capacity for them as well as boost up existing effective interventions and implementation. Additionally, NCD prevention in Thailand should be integrated with other public-health interventions and prevention of NCDs’ risk factors.